Analisis Kepuasan Konsumen dalam Pembelian Sayur Segar Secara Online pada Platform Sayurbox di Kota Denpasar (Jurnal Agribisnis dan Agrowisata, 2026)
Analysis of Consumer Satisfaction in Purchasing Fresh Vegetables Online on the Sayurbox Platform In Denpasar City. The company produces goods and services according to the needs and desires of consumers in order to achieve consumer satisfaction. Vegetables are the food needs of the community needed to meet daily nutrition in order to maintain a healthy body. Consumer satisfaction is very important for a business, if a customer is satisfied with what is being sold, they will become loyal customers and will recommend it to others. The object of this research is consumers selling fresh vegetables online, especially at SayurBox. This research is located in Denpasar City, Bali Province. The data collection method used was a questionnaire distributed to 30 consumers who live in Bali and have shopped at SayurBox at least once a month. The data analysis technique used is Importance-Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that the value of the Customer Satisfaction Index (CSI) for consumers using the SayurBox platform was 89.43%. This means that customers are very satisfied with the service for purchasing vegetables online on the SayurBox platform.
Keywords: customer satisfaction index; importance-performance analysis; customer satisfaction; fresh vegetables